An evaluation model for the implementation of hospital information system in public hospitals using multi-criteria-decision-making (MCDM) approaches - Esfahani, Ali Aliakbar; Ahmadi, Hossein; Nilashi, Mehrbakhsh; Alizadeh, Mojtaba; Bashiri, Azadeh; Abbasi Farajzadeh, Mohsen; Shahmoradi, Leila; Rasouli, Hamid Reza; Hekmat, Moustafa (International Journal of Engineering and Technology, 2017)
Background: Hospital Information System (HIS) is implemented to provide high-quality patient care. The aim of this study is to identify significant dimensional factors that influence the hospital decision in adopting the HIS.Methods: This study designs the initial integrated model by taking the three main dimensions in adopting HIS technology. Accordingly, DEMATEL was utilized to test the strength of interdependencies among the dimensions and variables. Then ANP approach is adapted to determining how the factors are weighted and prioritized by professionals and main users working in the Iranian public hospitals, involved with the HIS system.Results: The results indicated that â€œPerceived Technical Competenceâ€ is a key factor in the Human dimension. The respondents also believed that â€œRelative Advantage," â€œCompatibilityâ€ and â€œSecurity Concernâ€ of Technology dimension should be further assessed in relation to other factors. With respect to Organization dimension, â€œTop Management Supportâ€ and â€œVendor Supportâ€ are considered more important than others.Conclusion: Applying the TOE and HOT-fit models as the pillar of our developed model with significant findings add to the growing literature on the factors associated with the adoption of HIS and also shed some light for managers of public hospitals in Iran to successfully adopt the HIS.